OCCUPATIONAL DISEASES IN FISH PROCESSING INDUSTRY WORKERS: AN INTEGRATIVE REVIEW - Ribeiro, Ana Luísa Reis; de Azevedo, Ana Paula Chein Bueno; Cohen, Simone Cynamon; Cardoso, Telma Abdalla de Oliveira (Seven Editora, 2025)
The evolution of the fish processing industry, with technological innovations and organizational changes, contrasts with the scarce information on the health problems that can affect workers. In this sense, this study analyzes the main occupational diseases in the fish processing industry production sector. To this end, we conducted an integrative review, collecting information from the databases Lilacs, Medline/PubMed, SciELO, CINAHL, Embase, ScienceDirect, Scopus, and Web of Science. The guiding question was, “What are the main diseases affecting workers in the production sector of the fish processing industry?” We selected 41 articles that met the selection criteria, and the results and discussion were presented descriptively for their analysis, with diseases grouped into major groups. We observed that the studies ranged from reports of symptoms and health complaints to the diagnosis of occupational diseases. Furthermore, we identified that workers are affected by several health problems, such as respiratory and ocular diseases, musculoskeletal disorders, dermatoses, injuries, and less documented diseases such as hearing loss, hypothermia, hernia, and Raynaud’s syndrome. Evidently, respiratory symptoms and musculoskeletal complaints were the most frequently reported in the findings. We concluded that workers are exposed to different risk agents in the industry and that there are still few studies on the environmental and organizational conditions and the illness of workers in this production sector. We underscore the importance of expanding research and implementing prevention policies to protect workers’ health. DOI: https://doi.org/10.56238/sevened2025.037-037